Functional characterization of a putative Plasmodium falciparum calcium/hydrogen antiporter pfcha - Guiguemde, Wendyam Armand (2005)
SUMMARY Despite substantial efforts to control the spread of malaria, this infectious disease is still a major global health problem as chemotherapy of malaria parasites is limited by established drug resistance and lack of novel affordable treatment options. To combat malaria, identification and characterization of essential genes are needed. Although the calcium metabolism is very important in the life of P. falciparum, little is known about the genes which regulate the transport of calcium. With the release of the P. falciparum genome, a putative calcium hydrogen antiporter has been identified. To understand the role of this gene in the calcium metabolism of P. falciparum and to evaluate it as a drug target, we describe here the functional characterization by the heterologuous expression of this putative calcium hydrogen antiporter in Xenopus oocytes and in a S. cerevisiae strain which is deficient for the yeast vacuolar calcium hydrogen antiporter VCX1. The putative 441-residue protein, which we designate PfCHA, is predicted to contain 11 membrane-spanning segments and is related to the calcium exchanger family. Expression of pfcha in Xenopus oocytes resulted in a higher and pHdependent uptake of pfcha expressing oocytes, in comparison with control oocytes. External pH estimation showed that the calcium uptake was coupled to extrusion of protons out of the oocytes. In other experiments, we found that PfCHA has an antiport activity which is linear with time, unidirectional and electrogenic. Moreover PfCHA was inhibitable by La3+, a calcium transporter competitor, and was moderately inhibited by a sodium calcium exchanger inhibitor KB-R7943. This inhibitor showed also a moderate inhibition on parasite growth in culture. In contrast to the Xenopus oocytes, expression of pfcha in yeasts mutants defective in the Ca2+ transport resulted in a weakly complementat ion of the calcium tolerance. Our subcellular experiments suggested that PfCHA was localized to the yeast vacuole. These results confirm that PfCHA is a calcium hydrogen antiporter and we speculate that PfCHA could be a potential drug target. Further studies are needed to localize it in the parasite and to evaluate it as a drug target.